2022
DOI: 10.4142/jvs.21235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis E virus antibodies in cattle in Burkina Faso associated with swine mixed farming

Abstract: Background Endemic circulation of human-specific hepatitis E virus (HEV) genotypes 1 and 2 may occult the importance of sporadic zoonotic HEV transmissions in Africa. Increasing numbers of studies reporting anti-HEV antibodies in cattle and the discovery of infectious HEV in cow milk has raised public health concern, but cattle exposure has seldom been investigated in Africa. Objectives This study aimed at investigating the role of cows in the epidemiology of HEV in Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
13
2
Order By: Relevance
“…Another study Burkina Faso showed that pigs that are associated with cattle make them more susceptible to contracting the virus [22]. No significant association was observed between age group of pregnant women in this study and IgG detection, similar study pointed at this [23], but different from those recorded in India by [24].…”
Section: Discussioncontrasting
confidence: 65%
“…Another study Burkina Faso showed that pigs that are associated with cattle make them more susceptible to contracting the virus [22]. No significant association was observed between age group of pregnant women in this study and IgG detection, similar study pointed at this [23], but different from those recorded in India by [24].…”
Section: Discussioncontrasting
confidence: 65%
“…In domestic ruminants, HEV prevalence appears to be higher in rural areas with traditional mixed farming systems consisting of family-based small-sized farms hosting pigs and other domestic animals—a favorable epidemiological picture that may foster inter-species interactions [ 26 , 31 , 49 , 58 , 60 ]. In a recent study in Burkina Faso [ 45 ], cattle seropositivity was significantly associated with the presence of pigs on the same farm, suggesting the role of swine as risk factors [ 45 ]. However, this is not always the case, since Geng et al [ 55 ] did not detect HEV in the faeces and milk of cows reared on mixed farms or neighboring farms with pigs in the Hebei province of China [ 55 ], nor in Belgium, where viral RNA was not detected in cow fecal and milk samples despite being collected on a mixed farm in which HEV infection of swine had been demonstrated [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Gt3 HEV strains were detected in cows and goats of Assiut Village, Egypt, where pig farms are not common; even in the area housing pig farms, mixing of pigs and cows is uncommon due to religious beliefs [ 44 , 63 ]. Accordingly, HEV transmission to domestic ruminants could be due to several factors, including husbandry practices, type and intensity of inter-species contacts as well as hygiene on the farms and handling/management of HEV-contaminated manure produced by different animal species [ 44 , 45 ]. In a survey performed in the Czech Republic [ 65 ], it was speculated that pastures contaminated by HEV-positive wild animals (wild boars, red deer, roe deer and mouflons) could be the source of infection for small ruminants in which HEV RNA was detected in raw milk samples [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, only a few epidemiological studies on HEV infections in pigs have been carried out in African countries. The first findings were reported from Democratic Republic of the Congo [ 14 ], Madagascar [ 11 ], Nigeria [ 15 ], Cameroon [ 16 , 17 , 18 ], South Africa [ 19 , 20 , 21 ], Burkina Faso [ 22 ], Zambia [ 23 ], Ethiopia [ 24 ], and Ghana [ 25 ]. This is the first study to test pig samples from Sierra Leone for the presence of HEV, providing new insights into the spread of the virus in the country’s pig population.…”
Section: Introductionmentioning
confidence: 99%